ДЕЯКІ ПРОБЛЕМИ ВПРОВАДЖЕННЯ ІНФОРМАЦІЙНИХ ТЕХНОЛОГІЙ У НАВЧАЛЬНОМУ ПРОЦЕСІ (Педагогіка вищої та середньої школи, 2006)
This article is devoted to the basical organizational problems of for mulation electronic information trends in educational process.